Constructing NCuS Interface Chemical Bonds over SnS2 for Efficient Solar‐Driven Photoelectrochemical Water Splitting. Issue 3 (21st November 2022) - Zhang, Chengming; Wang, Meng; Gao, Kaiyue; Zhu, Haibao; Ma, Jie; Fang, Xiaolong; Wang, Xiufang; Ding, Yi
Abstract: The restricted charge transfer and slow oxygen evolution reaction (OER) dynamics tremendously hamper the realistic implementation of SnS2 photoanodes for photoelectrochemical (PEC) water splitting. Here, a novel strategy is developed to construct interfacial NCuS bonds between NC skeletons and SnS2 (CuNC@SnS2 ) for efficient PEC water splitting. Compared with SnS2, the PEC activity of CuNC@SnS2 photoelectrode is tremendously heightened, obtaining a current density of 3.40 mA cm 2 at 1.23 V RHE with a negatively shifted onset potential of 0.04 V RHE, which is 6.54 times higher than that of SnS2 . The detailed experimental characterizations and theoretical calculation demonstrate that the interfacial NCuS bonds enhance the OER kinetic, reduce the surface overpotential, facilitate the separation of photon‐generated carriers, and provide a fast transmission channel for electrons. This work presents a new approach for modulating charge transfer by interfacial bond design in heterojunction photoelectrodes toward promoting PEC performance and solar energy application. Abstract : A simple strategy is developed to construct interfacial NCuS bonds between NC skeletons and SnS2 . The NCuS bonds enhance the oxygen evolution reaction kinetics, boost the separation of photon‐generated carriers, and provide a fast transmission channel for electrons. So, the CuNC@SnS2 photoanode material shows excellent performance in photoelectrochemical water splitting.